Review on the development of defect-free and ultrathin- skinned asymmetric membranes for gas separation through manipulation of phase inversion and rheological factors - Ismail, Ahmad Fauzi; Lai, Ping Yean (Wiley Periodicals, Inc., 2003)
Development of high-performance asymmetric membranes is a major breakthrough in membrane technology. A comprehensive study on original concepts and new advances in membrane formation process is necessary to generate defect-free and ultrathin-skinned asymmetric membranes with superior performance for gas separation process. Correlation of rheological factors with primary-phase inversion process is a novel approach in membrane research that provides a potential platform to improve membrane performance. The former controls general morphology of membrane, whereas the latter further affects molecular orientation in membrane